Efektivitas Program Pemberdayaan Masyarakat Bagi Pelaku Usaha Kecil Menengah di Kabupaten Sikka (Studi Kasus PNPM Mandiri Perdesaan Kecamatan Nita Tahun 2010) - Anitha Nurak; Andi Gau Kadir; Muhammad Tamar (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2010)
Abstract: The study was done in order to obtain a description and explanation of the implementation of PNPM Mandiri Rural community development in the district in Sikka district Nita. To obtain an explanation of the effectiveness of PNPM Mandiri Rural community development in the district in Sikka district Nita. To determine the factors that influence community development in District Nita Sikka regency. Data collection is done by way of interviews, documentation, and observation to support the acquisition of data.Based on the analysis of data showed that the implementation of PNPM Mandiri Rural District in community development in Small and Medium Enterprises Nita especially those carried out on non-physical development. Consists of PNPM Mandiri program implemented in the field of Rural Productive Economic Enterprises (UEP) and the Special Women's Savings and Loans (SPKP). With indicators of participation in the planning of a) participation in brainstorming, b) active in submitting proposals / ideas, participation in the implementation of a) the willingness to take the time / and the power, b) willingness to provide material / materials, participation in the maintenance process with activity in the maintenance of the activity.Keywords: empowerment, participation, developmentAbstrak: Penelitian ini bertujuan untuk memperoleh gambaran dan penjelasan tentang pelaksanaan PNPM Mandiri Perdesaan dalam pemberdayaan masyarakat di Kecamatan Nita Kabupaten Sikka, efektivitas PNPM Mandiri Perdesaan dalam pemberdayaan masyarakat, serta faktor-faktor yang mempengaruhi pemberdayaan masyarakat tersebut.Pengumpulan data yang dilakukan dengan cara wawancara, dokumentasi, dan observasi untuk menunjang perolehan data. Berdasarkan hasil analisis data dikemukakan bahwa pelaksanaan PNPM Mandiri Perdesaan dalam pemberdayaan masyarakat di Kecamatan Nita terkhusus Usaha Kecil Menengah dilaksanakan pada pembangunan non fisik. Terdiri dari program PNPM Mandiri Perdesaan yang dilaksanakan di bidang usaha ekonomi produktif (UEP) serta simpan pinjam khusus perempuan (SPKP). Dengan Indikator partisipasi dalam pelaksanaan yakni a)kesediaan dalam meluangkan waktu/dan tenaga, b)kesediaan dalam menyediakan bahan /materi, c)partisipasi dalam proses pemeliharaan yakni dengan keaktifan dalam pemeliharaan hasil kegiatan.Kata kunci: pemberdayaan, partisipasi, pembangunan.